Das Mittelmeer und die deutsche Literatur der Vormoderne Transkulturelle Perspektiven - Quenstedt, Falk (De Gruyter, 2023)
Characteristic of the premodern Mediterranean world were the manifold connections between communities shaped by diverse traditions. German-speaking actors influenced these transcultural entanglements: as rulers, traders, spouses, refugees, soldiers, diplomats, prisoners, pilgrims. This volume thus inquires into the significance of the Mediterranean region for German literature and into the functions of its literary portrayals.